Blood-feeding patterns of native mosquitoes and insights into their potential role as pathogen vectors in the Thames estuary region of the United Kingdom - Brugman, V.A.; Hernández-Triana, L.M.; England, M.E.; Medlock, J.M.; Mertens, Peter P.C.; Logan, J.G.; Wilson, A.J.; Fooks, A.R.; Johnson, N.; Carpenter, S. (BioMed Central, 2017)
Background: The range of vertebrate hosts on which species of mosquito blood-feed is an important parameter for identifying potential vectors and in assessing the risk of incursion and establishment of vector-borne pathogens. In the United Kingdom, studies of mosquito host range have collected relatively few specimens and used techniques that could only broadly identify host species. This study conducted intensive collection and analysis of mosquitoes from a grazing marsh environment in southeast England. This site provides extensive wetland habitat for resident and migratory birds and has abundant human nuisance biting mosquitoes. The aim was to identify the blood-feeding patterns of mosquito species present at the site which could contribute to the transmission of pathogens. Methods: Twice-weekly collections of mosquitoes were made from Elmley Nature Reserve, Kent, between June and October 2014. Mosquitoes were collected using resting boxes, by aspiration from man-made structures and using a Mosquito Magnet Pro baited with 1-octen-3-ol. Blood-fed specimens were classified according to the degree of blood meal digestion using the Sella scale and vertebrate origin determined using sequencing of a fragment of the mitochondrial cytochrome C oxidase subunit I gene. Mosquitoes that were morphologically cryptic were identified to species level using multiplex PCR and sequencing methods. Results: A total of 20,666 mosquitoes of 11 species were collected, and 2,159 (10.4%) were blood-fed (Sella scale II-VI); of these 1,341 blood-fed specimens were selected for blood meal analysis. Vertebrate origin was successfully identified in 964 specimens (72%). Collections of blood-fed individuals were dominated by Anopheles maculipennis complex (73.5%), Culiseta annulata (21.2%) and Culex pipiens form pipiens (10.4%). Nineteen vertebrate hosts comprising five mammals and 14 birds were identified as hosts for mosquitoes, including two migratory bird species. Feeding on birds by Culex modestus and Anopheles atroparvus populations in England was demonstrated. Conclusions: This study expands the vertebrate host range of mosquitoes in the Thames estuary region of the UK. Feeding on both resident and migratory bird species by potential arbovirus vectors including Cx. pipiens f. pipiens and Cx. modestus indicates the potential for enzootic transmission of an introduced arbovirus between migratory and local bird species by native mosquito species.